Effect of Packaging Type and Storage Time on the Quality Characteristics of Chicken Nugget Substituted with Jack Bean (Canavalia ensiformis L.) Tempeh Flour - Sarah Giovani; Zahra Ismi Oktafiani; Ema Komalasari; Agus Setiyoko (Diponegoro University, 2024)
Chicken nuggets with jack bean tempeh flour substitution are a type of perishable food, thus having a short shelf life. The shelf life of chicken nuggets with jack bean tempeh flour substitution and its quality were affected by the storage conditions. This study aimed to determine the effect of packaging type and storage time during 20 days of cold storage under vacuum packaging condition on the quality characteristics of chicken nuggets with jack bean tempeh flour substitution. The research design consisted of two factors, the first factor was packaging type (nylon/polyethylene (PE), nylon/polyethylene (PE)/polyamide (PA), and polyethylene (PE)/polyamide (PA)) and the second factor was storage time (0 day, 5 days, 10 days, 15 days, and 20 days). The results showed that the packaging type and storage time significantly affected the quality characteristics of chicken nuggets with jack bean tempeh flour substitution (p < 0.05). In conclusion, PE/PA was the most suitable plastic packaging for maintaining the quality characteristic of chicken nuggets substituted with jack bean tempeh flour during 20 days of cold storage under vacuum packaging conditions. The physical and chemical quality of chicken nuggets substituted with jack bean tempeh flour on the 20th day of storagewere pH of 6.43, cooking loss of 9.85%, moisture content of 39.46%, protein content of 24.51%, TVBN content of 16.44 mg N/100 g, and TPC of 5.36 log cfu/g. Meanwhile, the result of the sensory evaluation showed that scores for attributes were color 3.63, aroma 3.45, taste 3.5, texture 3.29, and overall 3.53 (like slightly) on the 20th day of storage.